Quality of Experience and Users Elasticity Considerations for Modelling Competition between Service Providers in NGN - Radonjic, V.; Ljubisavljevic, A. Kostic; Stojanovic, M. (Elektronika ir Elektrotechnika, 2012)
In next generation networks, service providers should take into consideration not only quality of service but also quality of users’ experience aspects. In this paper we propose Cournot game for modelling competition between two service providers offering the same NGN service to users classified according to elasticity criterion. The proposed model includes quality of service parameters within users’ utility functions and total users’ demand as a function of quality of experience parameters. For this model we have analyzed the price setting through three distinctive cases. The numerical results have shown that service providers’ profits are greatly affected by both quality of experience and users’ elasticity. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2640